Desarrollo de un sistema de control para el horno a gas del Laboratorio de Fundición de la UPS. - Quiroga Ocampo, Josué Esteban (2018)
The Nabertherm brand crucible furnace is in the Casting Laboratory of the Mechanical Engineering Career at the (UPS) South Campus. Aluminum is melted in this furnace using manual control for academic purposes. Due to the lack of automation, resources are lost because the user must be aware of the process. In the present project of titillation, a system of control of temperature for the oven to gas was designed and implemented, where the reference is the value of the temperature and it was controlled with the variables: mixture of gas flow, air and activation of the gas passage solenoid valve to produce the flame. First, the characterization of the melting furnace and of the burner that produces the flame was carried out, the flow diagram of the aluminum melting process and the diagrams of the electronic elements of the control board were elaborated. Appropriate control was selected for the process and the materials that meet the functional and economic needs. Subsequently, the programming of the PLC and the HMI was carried out, after which the electronic elements were connected, culminating with implementation. In the end, its operation was verified by means of operation tests and the results were documented in the written work. It was concluded that to produce a suitable flame to heat the crucible furnace, the variables: air flow, gas and pressure are calibrated according to the melting stage.